Industrial Policy Priorities of Russia in the Context of Challenges of the Fourth Industrial Revolution. Part 2 - Romanova, Olga Aleksandrovna (Economy of Regions, 2018)
The article emphasizes the relevance of the digital economy development as one of the most important directions of the fourth industrial revolution. It is significant for a breakthrough in science and technology, social and economic development. I prove that the industrial policy is a reliable instrument for supporting digital economy. The followingfactors define the priorities of industrial policy: the level of socio-economic development of the country, the existing model of economic development, an image of the country’s future. I consider the evolution of the industrial policy priorities in Russia. In current situation, the essentially new priority is the support of digital economy. I find that pro-active digital economy formulation and management in collaboration of all branches of the government as well as the development of digital economy together with sector programmes and programmes of innovative development, etc. are of great importance. I have suggested steps, which could make the Industry Development Fund to support the new priorities connected with digital economy development. Furthermore, I have developed proposals on adjusting provisions, which define the possibility to apply special investment contracts for stimulating the digital economy development. I have defined the main directions of staffing the digital economy. The article emphasizes that «digital transformation of the industry» radically changes the idea targets and subjects of industrial policy. So-called related industries, as the association of goods, individuals, and technologies within the industrial system, the structures based on such special type of business models as technological platforms and the human needs become a new targets of the industrial policy. During the fourth industrial revolution, a system of interaction between federal and regional authorities and various business associations as well as civil society institutions becomes the main subject of industrial policy. This predetermines a multi-actor character of the industrial policy. The requirements to leaders of the state and business structures have increased. Therefore, their responsibility for preventing negative social and ethical consequences of the implementation of new technology solutions.